Mind-body training and progressive muscle relaxation therapy on nurse with burnout syndrome - Rahmayanti, Asih Devi; Putra, Kuswantoro Rusca; Yuliatun, Laily (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2021)
Background: Nurse burnout could affect nurse’s professional competence. Either physical or emotional burnout was related to an ineffective individual coping and emotional intelligence. The nurse burnout could be coped with a direct intervention on the individuals who practically focused on the mind and body system. Purposes: This research was aimed to identify the effects of mind and body-based therapies (MBT and PMR) for nurse burnout. Methods: This research was quasi-experimental with two groups pretest-posttest design. The sample of this study was 50 nurses in the medical-surgical wards who were divided into intervention MBT and PMR with a simple random sampling technique. Collecting data using burnout syndrome measurements on nurses applied pre and post-intervention, which was analyzed by Wilcoxon and Mann-Whitney test. Results: The mean value of the burnout subscale decreased significantly (emotional exhaustion and depersonalization) and increased (personal accomplishment) after the MBT and PMR programs (p<0.05). The comparison of effect between the two intervention groups on nurse burnout syndrome found no significant positive difference in the mean scores (p>0.05). Conclusions: Mind body-based therapies (MBT and PMR) could reduce burnout syndrome significantly.